2015
DOI: 10.1057/crr.2014.18
|View full text |Cite
|
Sign up to set email alerts
|

Agenda Building and Agenda Setting in Business: Corporate Reputation Attributes

Abstract: Grounded in an agenda-building and agendasetting framework, the current study explored the transfer of salience relationships among public relations materials, news media coverage and online public communications in a business communication context. A total of 2,576 communication messages were analyzed in terms of the dominant business corporation (object), corporate attributes (substantive attributes) and the tone of attributes (affective attributes). Our results showed that the transfer of salience relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 28 publications
0
22
0
1
Order By: Relevance
“…Rumusan delapan agenda pembangunan dilatarbelakangi oleh berbagai isu strategis pembangunan yang dikaji secara mendalam, menjadi acuan dalam perencanaan dan pelaksanaan pembangunan. (Cohen, 1963:13, McCombs dan Shaw, 1972 dalam (Kim et al, 2015). Agenda setting oleh ketiga surat kabar tentang pelaksanaan delapan agenda pembangunan provinsi NTT tidak sekedar mempublikasikan berbagai isu atau realitas tetapi menunjukkan bagaimana eksistensi surat kabar dalam menyikapi jalannya pembangunan di provinsi NTT.…”
Section: Pendahuluanunclassified
“…Rumusan delapan agenda pembangunan dilatarbelakangi oleh berbagai isu strategis pembangunan yang dikaji secara mendalam, menjadi acuan dalam perencanaan dan pelaksanaan pembangunan. (Cohen, 1963:13, McCombs dan Shaw, 1972 dalam (Kim et al, 2015). Agenda setting oleh ketiga surat kabar tentang pelaksanaan delapan agenda pembangunan provinsi NTT tidak sekedar mempublikasikan berbagai isu atau realitas tetapi menunjukkan bagaimana eksistensi surat kabar dalam menyikapi jalannya pembangunan di provinsi NTT.…”
Section: Pendahuluanunclassified
“…Specifically, the attributes can be examined from the substantive or affective dimension. Substantive attributes such as the personality and policy position of candidates refer to the cognitive characteristics of an object (Kiousis et al, 2015), while affective attributes refer to the emotional characteristics of an object such as the tonality of an issue (i.e., positive, negative or neutral tone) (Carroll & McCombs, 2003). Numerous studies (Curtin, 1999;Kiousis & Strömbäck, 2010;Kiousis et al, 2006Kiousis et al, , 2007Ku et al, 2003) have found that information subsidies influence not just which topics are covered by the media (first-level), but also how these topics are described (secondlevel).…”
Section: The Concept Of Agenda Buildingmentioning
confidence: 99%
“…Such first-level and second-level agenda building theories are mostly applied in democratic societies where interest groups and policy makers reach the public and influence their opinions by building mass media agendas (Berger, 2001;Kim et al, 2015, Kleinnijenhuis, Schultz, Utz, & Oegema, 2013. Democratic conditions for agenda building, however, seem not to be present in the RCSC case given the social and political situations in China.…”
Section: Agenda Building and Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Others have used the broader concept of ‘agenda building’, or ‘media agenda setting’ ( Denham, 2010 ), to study how media select and emphasize some organizations and/or issues over others, thereby mainly focusing on the impact of public relations on the news (e.g. Kim et al, 2015 ; Kiousis et al, 2007 ; Moon and Hyun, 2014 ; Ragas et al, 2011 ). A particular relevant research avenue that remains unexplored by these ‘agenda scholars’ interested in organizations is that of media agenda diversity.…”
mentioning
confidence: 99%